Surgical Replacement of Prolapsed Cloaca in an Indian Tent Turtle (Pangshura tentoria circumdata) – A Case Report - Vishvakarma, Shashank; Bajaj, Nitin K; Khan, Asad; Dawar, Meenakshi; Verma, Anjul (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Chelonians are basically diapsids which come under the class Reptilia of subphylum vertebrata. In reptiles they are kept in the order of Testudines which comprises turtles, terrapins and tortoises (Kuchling, 2012). The chelonian cloaca has extensive physiological interactions with both the bladder and large intestine, enabling fluid recycling, especially in uricotelic and hibernating species. The Indian tent turtle are vulnerable species and falls within appendix II of CITES, according to IUCN. This species is found in large rivers and in the small tributaries. This report presents a case of successful surgical replacement of prolapsed cloaca in a tent turtle at VCC, Jabalpur (MP) with minor complications.